2022
DOI: 10.1128/aem.01092-22
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Prototheca Microalgae in Aquatic Ecosystems with a Description of Three New Species, Prototheca fontanea, Prototheca lentecrescens, and Prototheca vistulensis

Abstract: The study investigates the occurrence of very rare and poorly studied microalgae of the genus Prototheca , potentially pathogenic to humans and animals, in different water environments. Given the potential hazard to human and animal health from exposure to water-inhabiting protothecae, the prevalence of the algae in aquatic habitats deserves an insightful examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…However, due to vast discrepancies in sampling across the diversity of Prototheca spp. between the aforementioned phylogenies and the current work, we believe them to be impossible to compare in detail – for instance, the most recent cytb -based reconstruction included seventeen P. ciferrii sequences, while the species P. paracutis or P. lentecrescens have not been included at all, simply because they have not been described at the time (Jagielski et al, 2022, 2019; Kunthiphun et al, 2019).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, due to vast discrepancies in sampling across the diversity of Prototheca spp. between the aforementioned phylogenies and the current work, we believe them to be impossible to compare in detail – for instance, the most recent cytb -based reconstruction included seventeen P. ciferrii sequences, while the species P. paracutis or P. lentecrescens have not been included at all, simply because they have not been described at the time (Jagielski et al, 2022, 2019; Kunthiphun et al, 2019).…”
Section: Resultsmentioning
confidence: 97%
“…Nonetheless, we are convinced that the facultatively pathogenic inclinations of Prototheca have not been the main driving force between the repeated loss of photosynthesis. Instead, it seems more plausible that forfeiting photosynthesis accompanied the transition of these microorganisms to low-light, high-TOC habitats, such as river sediments, demonstrated in a recent environmental survey (Jagielski et al, 2022) to be their important reservoir in nature. Still, as the Prototheca spp.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 currently recognized Prototheca species ( 2 , 3 , 4 ), five ( P. wickerhamii , P. blaschkeae , P. cutis , P. miyajii , and P. bovis ) have been implicated in human protothecosis, with P. wickerhamii being responsible for the bulk of the cases ( 5 7 ). The disease, which typically manifests in the form of a cutaneous, articular (olecranon bursitis), and systemic infection, remains rare; however, the number of cases has been increasing globally ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an increasing number of cases are reported worldwide, the impact of Prototheca infection on human and animal health is increasing. Prototheca has been isolated from natural water sources and artificial aquatic reservoirs (Jagielski et al, 2022). The primary source of Prototheca isolates is wastewater from cities, with P. wickerhamii being the most common isolate (Pore et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, a study on the occurrence of Prototheca in freshwater ecosystems identified P. wickerhamii (17/51, 33%) as the most abundant Prototheca microalga, followed by P. pringsheimii, P. cerasi, P. bovis, P. ciferrii, P. cookei, and P. zopfii. P. wickerhamii is the major isolate collected from rivers and streams in the environment (Jagielski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%